ANCAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) SEBAGAI SPESIES ASING INVASIF DI HUTAN KONSERVASI: Studi Kasus di Kampus IPB Darmaga, Bogor - Agus Hikmat; Ervizal A.M. Zuhud; Marwa Prinado (Media Konservasi, 2014)
Palm oil is potential become an alien invasive plant species based on important value index and distribution value in every community. Expansion of palm oil in Indonesia from big companies become an ecological threat for conservation area which benefit for protect biodiversity, especially the place which straight abut or around palm oil farm. This research due to identification of dominance palm oil and distribution pattern palm oil in IPB Darmaga. This research held in IPB Darmaga area which never planted palm oil by people from January to February 2011. Total sampling plot each in unit location is 25 plot. Determining the sample plot use systematic sampling with random start. The distribution pattern result from this research is palm oil have clumped pattern of distributed. Keyword: Alien species, Conservation forest, IPB Darmaga Campus, Palm oil, Invasive species.